The Application of Islamic Educational Philosophy in Congregational Dhuha Prayer Activities at MIN 5 Ngawi - Ari Abi Aufa; Muhammad Rofiiqul Umam (Global Education Journal, 2026)
In shaping an education, it is also recommended to be able to create an optimal achievement that not only transfers knowledge but also forms the character and noble personality of students. This study aims to discuss the application of Islamic educational philosophy carried out at MIN 5 Ngawi in the form of congregational dhuha prayer activities. Using descriptive qualitative field research methods, the results of the study indicate that the form of dhuha prayer activities carried out at MIN 5 Ngawi is carried out every morning before the learning process begins and is attended by all students from grades 1-6. This activity is accompanied by Islamic Religious Education teachers to monitor and provide direction to students. After the dhuha prayer activity is completed, a short surah memorization is carried out. This series of activities has character education value where, in the view of educational philosophy, it is interpreted as a form of integration between religious and societal values ​​and norms that are expected to later become provisions for students to grow and develop in the future